Wywiad z Radosławem Nowakowskim, przeprowadzony w foyer Biblioteki Jagiellońskiej w Krakowie 4.04.2024 roku, na parę godzin przed wernisażem wystawy artysty pt. Zawsze pomiędzy poza nad – książki Radosława Nowakowskiego (5–29.04.2024) - Błaszczak, Monika; Nowakowski, Radosław (Przestrzenie Teorii, 2024)
The interview with Radosław Nowakowski is a record of a conversation conducted by Monika Błaszczak before the opening of the exhibition of the artistąs works entitled Always between beyond above – books by Radosław Nowakowski (5–29.04.2024) at the Jagiellonian Library in Kraków. Nowakowski is a versatile creator, author of art books, essays, hypertext novels, actions, installations, exhibitions, performances, as well as a publisher, translator and musician. The interview was devoted to all aspects of his work, with a key emphasis on liberatory works and artistic books that co-created the Kraków exhibition.